Evaluating Spatiotemporal Variation of Groundwater Depth/Level in Beijing Plain, a Groundwater-Fed Area from 2001 to 2010 - Yuyan Zhou; Weihua Xiao; Jianhua Wang; Yong Zhao; Ya Huang; Jiyang Tian; Yan Chen (Advances in Meteorology)
Groundwater has always been a valuable resource in Beijing, facing a great decline of groundwater level during the past decades. However, few previous researches have revealed the spatial variation of groundwater level within Beijing Plain. In this study, spatiotemporal variation of groundwater level from 2001 to 2010 in Beijing Plain has been investigated. Factor analysis has been conducted to identify the primary influencing factor. Results showed that the groundwater level decreased by 8.41 m from 2001 to 2010, with a linear decreasing rate of 0.954 m per year averagely. Significant spatial variation characteristics have been detected. The north area suffered more groundwater depletion than the south part in general. The lowest groundwater level has been identified downstream Miyun Reservoir, central part of the Plain. Nevertheless, the most of the south part witnessed a slight revival between 2001 and 2010. This may be due to the differences of socioeconomic circumstances in the Plain. Three influencing factors, that is, “demand factor,” “supply factor,” and “loss factor,” have been identified in the water balance model. Eigenvalues of these factors are 3.563, 2.910, and 1.632, respectively, indicating that these factors influenced the groundwater system to various extents, with the demand factor being the primary one.